2005
DOI: 10.1108/01443570510613938
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing performance: evaluation and determinants

Abstract: Purpose -Many studies examine manufacturing performance along individual benchmarking dimensions. This study aims to develop a performance metric based on quality and output volume among other variables to assess a firm's manufacturing competitiveness in relation to its major rivals. Design/methodology/approach -The relative manufacturing performance is measured by data envelopment analysis (DEA). Several key manufacturing practices are examined for their impact on performance. They are research and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 35 publications
0
42
0
2
Order By: Relevance
“…It is suggested that organizational sustainability and success depends in part on the measurement and benchmarking of predictive upstream dimensions, indicators and measures within organizations [3], [4]. "Upstream" refers to developmental organizational areas, functions and networks that are at the conception stage of an organization's activities; for example, new product development (NPD), employee development, or technology development, in contrast to more downstream or output orientated activities such as manufacturing or service delivery [5], [6].…”
Section: Benchmarking and Zakat Orgnizationsmentioning
confidence: 99%
“…It is suggested that organizational sustainability and success depends in part on the measurement and benchmarking of predictive upstream dimensions, indicators and measures within organizations [3], [4]. "Upstream" refers to developmental organizational areas, functions and networks that are at the conception stage of an organization's activities; for example, new product development (NPD), employee development, or technology development, in contrast to more downstream or output orientated activities such as manufacturing or service delivery [5], [6].…”
Section: Benchmarking and Zakat Orgnizationsmentioning
confidence: 99%
“…Mixed results have been found. While the work of Laugen, Acur, Boer, and Frick (2005) and Pagell and Sheu (2001) found either no effects or very weak but positive effects of outsourcing, the work of Leachman, Pegels, and Shin (2005) and Dabhilkar and Bengtsson (2008) for the most part found a negative performance effect. However, all four studies found very strong performance effects regarding the other manufacturing practices.…”
Section: Previous Studies With a Wide Approachmentioning
confidence: 99%
“…This can give the buyer the false impression that the supply base is harming performance, when the real problem is the way the buyer manages the supply chain" (Abstract). Leachman et al (2005) found that R&D commitment and the ability to compress production time have a strong positive impact on manufacturing performance. Finally, Dabhilkar and Bengtsson (2008) showed that in comparison to outsourcing, practices related to the enhancement of manufacturing capability had a much stronger ability to predict improvements in operating performance.…”
Section: Previous Studies With a Wide Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there has long been a recognition of the differences in motivations, interests and priorities of managers from different functional areas (O'Leary-Kelly and Flores, 2002; Rhee and Mehra, 2006) which if not managed appropriately, in terms of strategic alignment (Skinner, 1969), can be a significant detriment to firm performance (Malhotra and Sharma, 2002). This has prompted calls for decision-support tools that increase understanding of the underlying processes in the adoption and implementation of new technologies (Baldwin et (Brown et al, 2007;Leachman et al, 2005). The role and importance of management decision-making in organisational evolution can not be underestimated.…”
Section: Introductionmentioning
confidence: 99%